Traumatic Tympanic Bulla Fracture in a Cat With Severe Head Trauma - Sanroman-Llorens, Fidel; Whyte, Ana; Godinho, Pedro; Castells, Enrique; Fraga, Eduardo (Frontiers in Veterinary Science, 2020)
A nine-year-old male European shorthair cat was referred to our practice with severe head trauma after suffering a road traffic accident (RTA). The patient presented marked facial swelling and multiple skin wounds and bruising, inspiratory dyspnea, palpable mandibular and maxillary fractures, serosanguinolent oronasal discharge and right eye exophthalmos and buphthalmos with loss of menace and pupillary reflex. After stabilizing the patient, a CT scan was performed under general anesthesia and an oesophagostomy tube was placed. The Scan revealed the presence of multiple right tympanic bulla fractures. Multiple mandibular, maxillary and palatine fractures were also present. The cat underwent surgery. Mandibular symphysis and maxillary fractures were stabilized using intraoral cerclage wire fixation reinforced with composite and the right eye was enucleated. The rest of the fractures were treated conservatively. A CT scan 4 months after the trauma was also performed. At this point, the maxillofacial fractures were healing properly, and a bone callus with fragments fusion of the right tympanic bulla fractures was evident. There was absence of abnormal content inside the right tympanic bulla. The patient recovered uneventfully with no neurological deficits. To the author´s knowledge this is the first case reporting a traumatic tympanic bulla fracture in the cat with case follow up, and the first case reported using CT as diagnostic imaging test.